2021
DOI: 10.2174/1874285802115010139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Escherichia albertii in Pediatric Urinary Tract Infections

Abstract: Background: There are insufficient data about the presence of E. albertii as a causative organism in urinary tract infection in pediatric patients. Objective: The present study aimed to detect E. albertii by polymerase chain reaction (PCR) for detection of uidA, mdh, and lysP genes among isolated E.coli from children with urinary tract infection. Methods: The present study was a cross-sectional retrograde study which was carried out on 100 isolates of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Other researchers, Afshin et al [38] and Zaki et al [39], also described cases of urinary tract infections with E. albertii as the etiological agent. In addition, a single case of E. albertii bacteremia was reported in an elderly woman with multiple comorbidities, possibly due to its ability to move from the intestinal lumen to other extraintestinal sites [35,40].…”
Section: Discussionmentioning
confidence: 96%
“…Other researchers, Afshin et al [38] and Zaki et al [39], also described cases of urinary tract infections with E. albertii as the etiological agent. In addition, a single case of E. albertii bacteremia was reported in an elderly woman with multiple comorbidities, possibly due to its ability to move from the intestinal lumen to other extraintestinal sites [35,40].…”
Section: Discussionmentioning
confidence: 96%
“…Afshin et al [ 113 ] and Zaki et al [ 114 ] reported five and seven cases of E. albertii -associated urinary tract infections, respectively. A single case of E. albertii bacteremia has been reported in an old lady with multiple comorbidities probably because of its ability to translocate from the intestinal lumen to other extraintestinal sites [ 5 , 34 , 115 ].…”
Section: Clinical Significance Of Escherichia Albertiimentioning
confidence: 99%
“…As with most bacteria, antimicrobial resistance is a major concern. Several strains of E. albertii have been shown to be resistant to a significant number of important antibiotics including tetracycline, macrolides except for azithromycin, lincosamides, ampicillin, penicillin G, oxacillin, gentamicin, ciprofloxacin, trimethoprim, sulfamethoxazole, fusidic acid, rifampicin, meropenenem, imipenem, and norfloxacin [ 26 , 38 , 50 , 51 , 67 , 90 , 114 ]. Moreover, multidrug-resistant E. albertii strains [ 67 ], that displayed resistance or encode resistance determinates to antibiotics from at least eleven classes have been reported [ 6 , 116 ].…”
Section: Clinical Significance Of Escherichia Albertiimentioning
confidence: 99%
See 1 more Smart Citation
“…Infection in humans could occur due to contact with these animals or the consumption of contaminated food. It has implicated gastrointestinal disease and several urinary tract infections (UTI) [ [8] , [9] , [10] ]. The incidence of bacteremia caused by E. albertii is generally uncommon and rare, with only one reported case in the literature [ 11 ].…”
Section: Introductionmentioning
confidence: 99%